Three-dimensional right-ventricular regional deformation and survival in pulmonary hypertension. (15th June 2017) - Moceri, Pamela; Duchateau, Nicolas; Baudouy, Delphine; Schouver, Elie-Dan; Leroy, Sylvie; Squara, Fabien; Ferrari, Emile; Sermesant, Maxime
Abstract: Aims: Survival in pulmonary hypertension (PH) relates to right ventricular (RV) function. However, the RV unique anatomy and structure limit 2D analysis and its regional 3D function has not been studied yet. The aim of this study was to assess the implications of global and regional 3D RV deformation on clinical condition and survival in adults with PH and healthy controls. Methods and results: We collected a prospective longitudinal cohort of 104 consecutive PH patients and 34 healthy controls between September 2014 and December 2015. Acquired 3D transthoracic RV echocardiographic sequences were analysed by semi-automatic software (TomTec 4D RV-Function 2.0). Output meshes were post-processed to extract regional motion and deformation. Global and regional statistics provided deformation patterns for each subgroup of subjects. RV lateral and inferior regions showed the highest deformation. In PH patients, RV global and regional motion and deformation [both circumferential, longitudinal, and area strain (AS)] were affected in all segments ( P  < 0.001 against healthy controls). Deformation patterns gradually worsened with the clinical condition. Over 6.7 [5.8–7.2] months follow-up, 16 (15.4%) patients died from cardio-pulmonary causes. Right atrial pressure, global RV AS, tricuspid annular plane systolic excursion, 3D RV ejection fraction, and end-diastolic volume were independent predictors of survival. Global RV AS  > −18% was the most powerful RV function parameter, identifying patients with a 48%-increased risk of death (AUC 0.83 [0.74–0.90], P  < 0.001). Conclusion: Right ventricular strain patterns gradually worsen in PH patients and provide independent prognostic information in this population.